The Influence of Human Resource Planning on Teacher Performance at Harapan Sejahtera Private Christian Vocational School - Waruwu, Novtriman; Waruwu, Suka'aro; Hulu, Fatolosa; Waruwu, Meiman Hidayat (Journal of Management, Economic, and Accounting, 2025)
Human Resource Planning (HRP) is a systematic process for identifying, developing, and allocating human resources within an organization toachieve its goals and objectives. This study aims to investigate the influence of human resource planning (HRP) on teacher performance at SMKSwasta Kristen Harapan Sejahtera.This research employs a quantitative method with data collection techniques through questionnaires. The study was conducted at SMK SwastaKristen Harapan Sejahtera with a sample size of 30 respondents. The findings indicate that human resource planning has a significant influenceon teacher performance, both directly and indirectly. Based on the Coefficient of Determination test, the obtained Adjusted R Square value is0.311 or 31.1%. This result shows that the Human Resource Planning variable affects Teacher Performance by 31.1%, while the remaining 68.9%is influenced by other variables outside this study. Overall, the results suggest that Human Resource Planning (X) significantly influences TeacherPerformance (Y), as evidenced by the t-test result of 4.789 > 0.05.This study highlights the importance of human resource planning in improving teacher performance and achieving effective educational goals.